La gentrification et l’incendie criminel dans trois quartiers de Montréal - Therrien, Fanny; Vallée, Luc; Dupuis, Stéphane (Assurances)

(untitled) (HEC Montréal, 1996)
In the Greater Montreal area, the gentrification of the Plateau Mont-Royal/Centre-Sud and South-West districts and the City of Verdun has been accompanied by an increase in fires, many of a criminal nature. The governmental and municipal programs which favor urban revival in certain districts of Montreal and insurance companies must take into account this phenomenon which is related to gentrification.